2020
DOI: 10.3390/foods9060710
|View full text |Cite
|
Sign up to set email alerts
|

Application of ATR-FT-MIR for Tracing the Geographical Origin of Honey Produced in the Maltese Islands

Abstract: Maltese honey has been produced, marketed, and sold as an exclusive local gourmet food product for countless years. Yet, thus far, no study has evaluated the individuality of this local food product. The evaluation of the parameters and properties which characterise the provenance and floral source of honey have been the subject of various studies worldwide, owing to the price and potential beneficial properties of this food product. Models analysing the potential of attenuated total reflection mid-infrared (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Furthermore, MIR methods have been reported for the authentication, provenance, and traceability of various food products, e.g., fruit purees [25], honey [26], and cocoa bean shell [27]. Recently, Formosa et al [28] applied attenuated total reflection mid-infrared (ATR-FT-MIR) spectroscopy in discriminating and classifying local honey from that of foreign origin. A high accuracy (>95%) was achieved by using different modeling algorithms with spectral pre-treatments, confirming the capability of MIR in the context of the authentication of honey samples.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MIR methods have been reported for the authentication, provenance, and traceability of various food products, e.g., fruit purees [25], honey [26], and cocoa bean shell [27]. Recently, Formosa et al [28] applied attenuated total reflection mid-infrared (ATR-FT-MIR) spectroscopy in discriminating and classifying local honey from that of foreign origin. A high accuracy (>95%) was achieved by using different modeling algorithms with spectral pre-treatments, confirming the capability of MIR in the context of the authentication of honey samples.…”
Section: Introductionmentioning
confidence: 99%
“…The previously reported studies emphasized the potential of IR spectroscopy in the differentiation of the botanical and geographical origins of honey [ 19 , 20 , 21 ], but according to our knowledge, no studies related to the differentiation of honey harvesting years have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…For the geographical authentication, Formosa et al used spectral transformations, variable selection and PLS-DA to successfully classify the provenance of 21 local and 49 non-local honey samples [ 20 ]. Other reported studies present the use of chemometric tools (PLS, PCA, LDA) in NIR spectroscopic studies to differentiate honey according to its geographical origins [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the 31 samples, seven were bought from the local market, and the rest were collected directly from the beekeepers. The study also investigated the composition of 48 non-local samples used in a recently completed study on the chemical profiling of honey produced in the Maltese islands by Formosa (2017) [ 27 ]. A total of 81 phenolic extracts, with the majority extracted from the investigated whole fraction honey samples, were studied with 1 H zg30 NMR.…”
Section: Methodsmentioning
confidence: 99%
“…A number of different studies have been carried out on the Maltese honey based on physicochemical parameters; these included HMF content, diastase and proline levels, total phenolic content, and sugar composition [ 25 , 26 ]. More recently, a comprehensive study based on the attenuated total reflection mid-infrared (ATR-FT-MIR) spectroscopy showed that it was possible to discriminate and classify local honey from that of non-local samples highlighting the authenticity of the Maltese honey [ 27 ].…”
Section: Introductionmentioning
confidence: 99%